2004
DOI: 10.1093/glycob/cwh073
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates act as receptors for the periodontitis-associated bacterium Porphyromonas gingivalis: a study of bacterial binding to glycolipids

Abstract: In this study we show for the first time the use of carbohydrate chains on glycolipids as receptors for the periodontitis-associated bacterium Porphyromonas gingivalis. Previous studies have shown that this bacterium has the ability to adhere to and invade the epithelial lining of the dental pocket. Which receptor(s) the adhesin of P. gingivalis exploit in the adhesion to epithelial cells has not been shown. Therefore, the binding preferences of this specific bacterium to structures of carbohydrate origin from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…Both nonacid and acid carbohydrate chains are known to act as bacterial receptors [3,9,21,29,37,55,56]. In our previous study we showed for the first time that also the P. gingivalis strain FDC381 can utilize glycolipid sugar chains as potential bacterial receptors [20].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Both nonacid and acid carbohydrate chains are known to act as bacterial receptors [3,9,21,29,37,55,56]. In our previous study we showed for the first time that also the P. gingivalis strain FDC381 can utilize glycolipid sugar chains as potential bacterial receptors [20].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, binding to galabiosylceramide (Galα4Galβ1Cer), globotriaosylceramide (Galα4Galβ4Glcβ1Cer) and globotetraosylceramide (GalNAcβ3Galα4Galβ4Glcβ1Cer) are found (not shown) Table 1. Moreover, in our previous study, binding to gangliotriaosylceramide (GalNAcβ4 Galβ4Glcβ1Cer) and gangliotetraosylceramide (Galβ3Gal NAcβ4Galβ4Glcβ1Cer) was obtained [20].…”
Section: Bacterial Overlay Assaysmentioning
confidence: 93%
See 2 more Smart Citations
“…The adhesin domains of arg-gingipain A and lys-gingipain were shown to bind to epithelial cells, and the adhesin peptide A44 of the former has a high affinity for host FN (7,13). In addition to integrins and ECM proteins, P. gingivalis interacts with several other receptors (14)(15)(16). In the present study, we provide evidence that cell surface transglutaminase 2 (TG2) plays an essential role in the interaction of P. gingivalis with host cells.…”
mentioning
confidence: 74%